ANEURYSM OF THE INTERNAL JUGULAR VEIN: A SHORT LITERARY REVIEW AND OWN OBSERVATION - O. NEMATZODA; D.A. RAHMONOV; A.KH. ZUGUROV; F.SH. RASHIDOV; I.I. BOLTABAEV (Avicenna Tajik State Medical University, 2018)
Objective: The paper describes the case of successful diagnosis and surgical treatment of an aneurysm of the internal jugular vein (IJV) in a young patient.